PENGUKURAN EFIKASI DIRI, KONSEP DIRI DAN MOTIVASI PEMBELAJARAN PASCA MENGIKUTI KKN TEMATIK MBKM DALAM MEMBENTUK KEMANDIRIAN BELAJAR MAHASISWA - Aufa Izzuddin Baihaqi; Maharani Ikaningtyas (Halu Oleo University, 2022)
Education is very important and cannot be separated from life. Humans and education are two things that cannot be separated, because education is the key to the future of quality humans who are equipped with reason and mind. Independence in a person can be seen from several characteristics, including someone who is able to take decisions and take the initiative to overcome the problems at hand. The purpose of this study was to determine how self-efficacy, self-concept, and student motivation in influencing learning independence after participating in the Thematic Real Work Lecture (KKN-Tematik) Merdeka Learning Independent Campus (MBKM) program. This study uses a quantitative approach. Researchers used a 5-point linkert scale in measuring the results of the answers to the research questionnaire. Test data analysis using linear regression analysis. Based on the results of research that has been carried out by researchers, there are several conclusions. First, the results of this study have shown that there is a positive and significant influence between the variables of Self-Efficacy on Learning Independence. Second, the Self-Concept variable has a positive and significant effect on the Independent Learning variable. The three learning motivation variables have a positive and significant influence on learning independence